In the Right Place at the Right Time: Regulation of Cell Metabolism by IP3R-Mediated Inter-Organelle Ca2+ Fluxes - Ahumada-Castro, Ulises; Bustos, Galdo; Silva-Pavez, Eduardo; Puebla-Huerta, Andrea; Lovy, Alenka; Cárdenas, César (Frontiers in Cell and Developmental Biology, 2021)
In the last few years, metabolism has been shown to be controlled by cross-organelle communication. The relationship between the endoplasmic reticulum and mitochondria/lysosomes is the most studied, here inositol 1,4,5-triphosphate (IP3) receptor (IP3R)-mediated calcium (Ca2+) release plays a central role. Recent evidence suggests that IP3R isoforms participate in synthesis and degradation pathways. This minireview will summarize the current findings in this area, emphasizing the critical role of Ca2+ communication on organelle function as well as catabolism and anabolism, particularly in cancer.